Compliance and Violation of the Principles of Politeness in the Marlo-Keisya Podcast: "Don't Want It to End" on the Cataisee YouTube Channel - Fadkhul Mu’is; Iib Marzuqi; Irmayani Irmayani (EDUJAVARE: International Journal of Educational Research, 2026)
Politeness in language is an important thing that needs to be considered when communicating so as not to cause hurt, disappointment or feel disadvantaged. This research aims to find out the principle of linguistic politeness and the violation of the principle of linguistic politeness which is validly studied in academic studies. The method used in this study is qualitative descriptive. The analysis was carried out using the theory of politeness according to Leech which put forward six principles, namely the maxim of wisdom, the maxim of generosity, the maxim of praise, the maxim of humility, the maxim of agreement, and the maxim of sympathy as well as the form of violation of linguistic politeness, namely the violation of the maxim of wisdom, the violation of the maxim of generosity, the violation of the maxim of praise, the violation of the maxim of humility, the violation of the maxim of agreement and the violation of the maxim of sympathy. The data was obtained through the technique of watching and recording. Based on the results of the study, there were 51 conversations that complied with or violated language politeness. Compliance totaled 20 data with details: (1) 3 Maxim Wisdom Data, (2) 1 Maxim Generosity Data, (3) 7 Maxim Praise Data, (4) 5 Maximal Humble Data, (5) 3 Maximal Consensus Data, and (5) 1 Maximal Sympathy Data. A number of politeness violations were found. 31 data with details: (1) 6 data on violations of the maximum of wisdom, (2) 1 data on violations of the maximum of generosity, (3) 7 data of violations of the maximum of praise, (4) 0 data of violations of the maximum of humility, (5) 13 data of violations of the maximum of agreements, (6) 4 data of violations of the maximum of sympathy.